(untitled) (Update Dental College Journal, 2014)
Summary: Ewings Sarcoma of the body of the mandible is rare and can be mistaken as inflammation of dental origin.Here we presented a case of Ewings Sarcoma of afemale child of 2years and 3months old.After histological and immunohistochemical confirmation, patient was treatedby VAC and IE therapy alternatively.The reported case describes the clinical, radiological and histopathological findings of Oral Ewings Sarcoma with difficulties in management with initial response of treatment. DOI: http://dx.doi.org/10.3329/updcj.v3i1.17985 Update Dent. Coll. j: 2013; 3 (1): 46-48